Endoplasmic reticulum proteostasis: a key checkpoint in cancer - Oakes, Scott A. (Am J Physiol Cell Physiol, 2017)
The unfolded protein response (UPR) is an intracellular signaling network largely controlled by three endoplasmic reticulum (ER) transmembrane proteins, inositol-requiring enzyme 1α, PRK-like ER kinase, and activating transcription factor 6, that monitor the protein-folding status of the ER and initiate corrective measures to maintain ER homeostasis. Hypoxia, nutrient deprivation, proteasome dysfunction, sustained demands on the secretory pathway or somatic mutations in its client proteins, conditions often encountered by cancer cells, can lead to the accumulation of misfolded proteins in the ER and cause “ER stress.” Under remediable levels of ER stress, the homeostatic UPR outputs activate transcriptional and translational changes that promote cellular adaptation. However, if the ER stress is irreversible despite these measures, a terminal UPR program supersedes that actively signals cell destruction. In addition to its prosurvival and prodeath outputs, the UPR is now recognized to play a major role in the differentiation and activation of specific immune cells, as well as proinflammatory cytokine production in many cell types. Given the numerous intrinsic and extrinsic factors that threaten the fidelity of the secretory pathway in cancer cells, it is not surprising that ER stress is documented in many solid and hematopoietic malignancies, but whether ongoing UPR signaling is beneficial or detrimental to tumor growth remains hotly debated. Here I review recent evidence that cancer cells are prone to loss of proteostasis within the ER, and hence may be susceptible to targeted interventions that either reduce homeostatic UPR outputs or alternatively trigger the terminal UPR.